A construção estilística das identidades poéticas da cidade de Natal: um olhar bakhtiniano - Faria, Marilia Varella Bezerra de (2007)
The purpose of this work is to bring forward cultural identities of the city of Natal that are built upon representations contained in the work of Twentieth-Century Potiguar1 poets. We started out with the premise that the urban tissue owes its formation to the effect of the feelings produced and to the individuals that give shape to them, thus causing the city to abound with feelings and meanings that are relevant for both society and the individual. As cities and their identities may be studied and interpreted from different viewpoints, we have used in this study poetic discourse that functions as a memory to the city and takes shape out of a set of historically established social practices. Our research is situated within the area of Applied Linguistics, an area of knowledge focused mainly in language that is increasingly expanding its investigation limits in an interdisciplinary way. Therefore, this study is based on a social and historical model of language, with language construed as a discourse practice (Bakhtin and Circle), and presents an interface with cultural studies (Hall, Canclini), taking into account the fact that culture builds up values and brings forth differences in respect of the conditions under which such values and differences are produced. In this sense, we have tried to ―listen‖ to what the poets say, by understanding and interpreting the meanings produced by their discourse, in order to identify the formation of the identities of the city that arise out of distinct points of view and diverse stylistic marks. Analysis of these poetic utterances lead to multifold cultural identities of the city, ranging from a naive and multicolored Natal to a city that builds itself on its characters and on to an insurgent, usurped Natal